FEMINISME DALAM PUISI ABDUL WACHID BS - Teguh Trianton (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Feminism movement begins from two basic problems that faced by women, namely domestic violence (KDRT) andpolygamy. After that, feminism is thriving to all domain and aspect of human life. On next development, feminism movement is not onlymonopolized by women. Men that always accused as one of actors of gender bias, actually participate to defend women right (malefeminist), with every ways, media, and method. One of media that effective to construct feminism discourse is through literary works, one ofit are poem